Seven steps to master the interview and get the job [soundrecording] - Young, Stephen (Random House Audio Pub., 1994)
Provides a technique for increasing your effectiveness in preparing for and conducting yourself in the job interview. The steps in mastering the interview includes preparing a unique marketing cover letter, creating the "resume addendum" making the pre-interview positioning call structuring the summary correspondence, etc.